2012
DOI: 10.1002/j.2168-9830.2012.tb00045.x
|View full text |Cite
|
Sign up to set email alerts
|

Conceptual and Procedural Approaches to Mathematics in the Engineering Curriculum: Student Conceptions and Performance

Abstract: BACKGROUNDDemands by engineering faculties of mathematics departments have traditionally been for teaching computational skills while also expecting analytic and creative knowledge-based skills. We report on a project between two institutions, one in South Africa and one in Sweden, that investigated whether the emphasis in undergraduate mathematics courses for engineering students would benefit from being more conceptually oriented than the traditional more procedurally oriented way of teaching. PURPOSE (HYPOT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 26 publications
1
49
0
Order By: Relevance
“…Engelbrecht, Bergsten and Kågesten (2012) designed a questionnaire to investigate junior engineering students' achievement and views on mathematics tasks that were either conceptually or procedurally focused. The students found procedural tasks to be more common than conceptually focused tasks in their mathematics courses, while the latter were more common in engineering subjects; they also reported a higher confidence in their performance on procedural tasks.…”
Section: Conceptual and Procedural Approaches To Mathematicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Engelbrecht, Bergsten and Kågesten (2012) designed a questionnaire to investigate junior engineering students' achievement and views on mathematics tasks that were either conceptually or procedurally focused. The students found procedural tasks to be more common than conceptually focused tasks in their mathematics courses, while the latter were more common in engineering subjects; they also reported a higher confidence in their performance on procedural tasks.…”
Section: Conceptual and Procedural Approaches To Mathematicsmentioning
confidence: 99%
“…In our previous study (Engelbrecht et al, 2012) we investigated how second year engineering students respond to the conceptual-procedural distinction made in research, as discussed above. In the study presented here, we surveyed senior (4 th year) engineering students, comparing the results of these students with those of the junior students.…”
Section: Purpose Focus and Design Of The Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…17 Similar studies by Simpson and Zakaria found that conceptually-oriented students use linking words, like "then" and "because" to explain their solutions. 22 This indicates that they are confident about the solution and, unlike procedurally oriented students, do not resort to external authority to justify their solution.…”
Section: Procedural and Conceptual Understandingmentioning
confidence: 72%
“…There is also good reason to believe that the students, like those in the Chappell and Killpatrick study above, will be able to reconstruct the concepts at will and apply them in the future. 17 Ultimately, using everyday examples is a conscious action where affordances for conceptual understanding are designed into the course and not only left to the student to attain in future once they have reached mathematical maturity through procedural struggle.…”
mentioning
confidence: 99%